Quad‐Band Transmissive Metasurface: Quad‐Band Transmissive Metasurface with Linear to Dual‐Circular Polarization Conversion Simultaneously (Adv. Theory Simul. 8/2021). Issue 8 (6th August 2021) - Li, Zhuo Yue; Li, Si Jia; Han, Bo Wen; Huang, Guo Shuai; Guo, Ze Xu; Cao, Xiang Yu
Abstract : In article number 2100117, Si Jia Li and co‐workers propose a quad‐band dual‐circular transmissive metasurface to manipulate polarization of transmissive wave. The metasurface manipulates linear incident polarization waves into left‐hand and right‐hand circular polarization waves in different frequency bands simultaneously. The proposed transmissive metasurface can be utilized in multiband wireless communications and multifunctional dual‐circularly polarized antenna systems.